Pengaruh Motivasi Ekologis terhadap Perilaku Pro Sosial yang Dimediasi Self Esteem - Gata Krisnawan; Rini Kuswati (Departement of Mathematics Education, 2024)
Self-esteem is an issue that is quite interesting to examine again. The aim of this research is to analyze the influence of ecological motivation on pro-social behavior and self-esteem and to analyze the influence of self-esteem on pro-social behavior. Apart from that, it is also to analyze self-esteem in mediating the influence of ecological motivation on social behavior. This research is quantitative research. In this research there are 15 question indicators, then the number of indicators is multiplied by 10 to obtain the minimum sample required. The information checking procedure used in this exploration is a Structural Equation Model (SEM) investigation with Smart Partial Least Square (PLS). Based on the research that has been carried out, this exploration can be concluded that ecological motivation has a positive effect on social behavior, so that the first hypothesis is recognized. Ecological motivation influences self-esteem, so the second hypothesis is recognized. The third hypothesis is supported because self-esteem has a positive and significant effect on behavior. Self-esteem intervenes in ecological motivation in supporting social behavior, so that the fourth hypothesis is recognized.